2020
DOI: 10.11606/issn.1678-4456.bjvras.2020.160956
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in bacteria isolated from pigs with respiratory clinical signs in Brazil

Abstract: Antimicrobial resistance is a current and important issue to public health, and it is usually associated with the indiscriminate use of antimicrobials in animal production. This study aimed to evaluate the antimicrobial susceptibility profile in bacterial isolates from pigs with clinical respiratory signs in Brazil. One hundred sixty bacterial strains isolated from pigs from 51 pig farms in Brazil were studied. In vitro disk-diffusion method was employed using 14 antimicrobial agents: amoxicillin, penicillin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For tetracycline, one Chinese study reported only 3.6% resistance (Zhou et al, 2010). Figure 27 indicates that even lower levels of resistance to tetracycline were detected in a Brazilian study (Serpa et al, 2020) and in a study on isolates from several European countries (El Garch et al, 2016). Importantly, the latter two studies would have had proportions of 57.1% and 47.7% if %R+I had been reported instead of %R.…”
Section: Results Of the Elr By Bacteriummentioning
confidence: 95%
See 2 more Smart Citations
“…For tetracycline, one Chinese study reported only 3.6% resistance (Zhou et al, 2010). Figure 27 indicates that even lower levels of resistance to tetracycline were detected in a Brazilian study (Serpa et al, 2020) and in a study on isolates from several European countries (El Garch et al, 2016). Importantly, the latter two studies would have had proportions of 57.1% and 47.7% if %R+I had been reported instead of %R.…”
Section: Results Of the Elr By Bacteriummentioning
confidence: 95%
“…For sulfonamides‐trimethoprim , the highest continent‐specific proportion of resistance (40.5%) was observed in South America, although based on only 42 isolates in one study from Brazil (Serpa et al., 2020 ). The lowest level of resistance was observed in Oceania represented by Australia (0.7% of 148 isolates).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation